Sistem Monitoring Photoplethysmograph Berbasis Zigbee Dan Labview - Hamdala Hamdala; Yusnita Rahayu; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Information heartbeat’s per minute and characteristics of heart rate is an essential to be monitored, it shows normal and abnormal condition of heart rate person’s characteristic. The normal heart rate is usually 60-100 bpm. This paper present a system monitoring based on Zigbee and Labview. It monitors heartbeat’s per minute, heart rate characteristic and respiratory rate per minute displayed though Labview GUI. From experimental the heartbeat’s of 89 bpm was obtained, it indicated in normal condition. The heart rate is less than 60 bpm indicated bicardia characteristic, and the heart rate is more than 100 bpm indicated tachicardi characteristic.Keywords: Photoplethysmograph, Heart’s rate, Respiratory rate, Labview, Heartbeat’s, Breathing